Pendampingan Pelatihan Pramuka Siaga Sebagai Bentuk Internalisasi Nilai-Nilai Karakter Siswa Kelas III SD Negeri Kaligangsa Kulon 01 - Mumpuni, Atikah; Tri Setiyoko, Didik (Universitas Nusantara PGRI Kediri, 2023)
Scouting activities in the independent curriculum are compulsory extracurriculars. However, at SD Negeri Kaligangsa Kulon 01, scouting activities are often hampered due to school conditions that are often inundated by water during the rainy season. Scouting activities also tend to focus on the material so that it feels boring. This method of community service activities is divided into two stages, namely training, preparation of activity design and implementation of scouting activities. The result of this community service is the design of game-based scouting activities. In addition, at the implementation stage, it was also found that the design of this activity was flexible so as to minimize the problems of scouting activities that occurred at SD Negeri Kaligangsa Kulon 01. Students in this community service activity can also develop cooperative, meticulous, and creative characters from the material of solving secret messages written using ciphers. The suggestions that can be given are, games as innovations in delivering scouting material, need to be adjusted to the material to be delivered.